Glycosylation of GETV E2 promotes pathogenesis in animal models - Ning Shi; Xiangshu Qiu; Jiaxin Tian; Xinyu Cao; Xiangyu Zhu; Bocheng Liu; Xuancheng Zhang; Hansi Zhang; Hualei Wang; Huijun Lu (Proceedings of the National Academy of Sciences, 2026)
Getah virus (GETV) is a mosquito-borne alphavirus. It has posed a threat to various livestock and humans during decades of evolution and spread. However, the viral determinants and mechanisms underlying enhanced virulence remain largely unknown. In this study, we identified E2-N262 glycosylation in GETV as an evolutionary adaptation that promotes receptor binding, innate immune evasion, and virulence. Using reverse genetics technology, we generated recombinant GETV strains―rSD2206 WT and the N262D substitution. In vitro, rSD2206 WT formed larger plaques and replicated more efficiently across multiple cell lines. Despite exhibiting enhanced pathogenicity, higher replication efficiency, and a weaker induction of host antiviral responses compared to the N262D virus in both mouse and suckling pig models, the rSD2206 WT virus retained immunogenicity. Mechanistically, we found that rSD2206 WT increased virion attachment and entry into host cells by enhancing binding affinity to both HS (a GETV attachment factor) and LDLR (a GETV receptor). In addition, the rSD2206 WT strain can evade the host’s antiviral response by interrupting the activation of interferon regulatory factor 3. Structural analysis revealed a significant reduction in binding free energy for rSD2206 WT. This reduction resulted in conformational changes within the E2 protein, which in turn enhanced its stability and subsequently strengthening its receptor-binding capacity. Ultimately, compared to N262D, rSD2206 WT exhibited increased replication in cells overexpressing LDLR, but significantly reduced replication in LDLR −/− mice. These results highlight the critical importance of proactive surveillance of GETV molecular evolution to prevent future outbreaks, which could provide the foundation for the development of attenuated vaccines.